REPRODUÇÃO DE ALGUMAS ESPÉCIES DE FITONEMATÓIDES EM NIGER (Guizotia abyssinica) - Rossi, Carlos Eduardo; Ferraz, Luiz Carlos Camargo Barbosa (REVISTA DE AGRICULTURA, 2015)
REPRODUÇÃO DE ALGUMAS ESPÉCIES DE FITONEMATÓIDES EM NIGER (Guizotia abyssinica)